The secret life of bugs: Going past the errors and omissions in software repositories - Aranda, Jorge; Venolia, Gina (2009 IEEE 31st International Conference on Software Engineering, 2009)
Every bug has a story behind it. The people that discover and resolve it need to coordinate, to get information from documents, tools, or other people, and to navigate through issues of accountability, ownership, and organizational structure. This paper reports on a field study of coordination activities around bug fixing that used a combination of case study research and a survey of software professionals. Results show that the histories of even simple bugs are strongly dependent on social, organizational, and technical knowledge that cannot be solely extracted through automation of electronic repositories, and that such automation provides incomplete and often erroneous accounts of coordination. The paper uses rich bug histories and survey results to identify common bug fixing coordination patterns and to provide implications for tool designers and researchers of coordination in software development.